Seminar Penguatan Pluralitas Mahasiswa Pendidikan Guru Sekolah Dasar Dengan Proyek Online Research - Rochim, Ahmad Abdul (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of the seminar is to foster an attitude of pluralism so that students respect one another. Community service seminars are conducted offline and online for students and lecturers of the STKIP Pangeran Dharma Kusuma Indramayu Elementary School Teacher Program. The positive sides of pluralism are: a) Differences in society will provide space for each individual to further develop in determining choices, ways, and goals of life. b) provide learning attitudes of maturity, and mutual respect because of the clash of differences, diversity and values that have different boundaries. Through seminars, online research and discussions, it is hoped that this will increase public knowledge about the importance of maintaining unity and tolerance. But it also increases knowledge of plurality application skills, and most importantly can overcome the problems experienced by the Indonesian nation regarding the presence of extremism that tries to undermine unity or does not recognize Indonesia's plurality.